Lost in transmission the role of attrition and input in heritage language development - Brehmer, Bernhard; Treffers-Daller, Jeanine, 1959- (Studies in bilingualism ;, 2020)
"Heritage speakers are a fascinating group of bilinguals with a unique profile. Living abroad as immigrants of the second generation, they speak the language of their own speech community (the heritage language) at home, and the societally dominant language in most other domains. What exactly they know about their heritage language continues to fascinate the research community as well as teachers and other practitioners working with this group. The different contributions cover a large variety of studies into heritage languages spoken in Europe and North America (including Chinese, Norwegian, Russian, Spanish and Turkish). The volume makes a key contribution to the description and explanation of variability in the outcomes of heritage language acquisition, taking into account a wide range of factors which impact on language acquisition. As comparisons are frequently made with monolinguals and foreign language learners, the volume is also highly relevant for researchers working in monolingual language acquisition and foreign language learning and teaching"--